THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE IN ISLAMIC BANKS - Ausat, Syed Amaar Ali (Jurnal Ekonomi & Studi Pembangunan, 2018)
Corporate governance refers to policies and mechanisms related to how the company is directed and controlled and looks at the Board of Directors and their characteristics for example. The focus of this study will be to investigate the relationship of corporate governance and financial performance for Islamic Banks. The corporate governance variables and financial data was collected using the Orisis database and looking through annual reports of the banks from 2013 to 2017. The sample comprised 12 listed Islamic banks from different countries and used a panel data approach with a set of 60 firm-year observations. The corporate governance variables selected included, board size, CEO duality, board independence and Shariah Supervisory Board size to test their effect of a firm’s performance measured by ROA and ROE. Other firm level characteristics such as size and age of the banks were included to reduce the amount of external influence throughout the study. Results were analysed using descriptive statistics, Pearson Correlation Matrix, Generalised Least Squared (GLS) regression and the Random Effect Model. The concluding results proved that there was a positive relationship between some corporate governance variables and a firm’s performance. Board size was reported as the most significant factor which affects financial performance as measured by ROA. However, interestingly CEO duality was also noted to be a significant factor which affected performance. This was seen for both performance measures; ROA and ROE. The remaining independent variables and control variables showed no significant correlation to a firm’s performance and that there must be external factors which explain performance. The results showed that corporate governance was a necessary consideration for improved performance.